Pengaruh Green Marketing, Consumption Value, dan Brand Image Terhadap Repurchase Intention Traditional Fusion Food Khas Bali Pada Restaurant di Provinsi Bali - Wijaya, I Putu Gede Dharma; Chrisyanti Dewi, Irra (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to examine the effect of green marketing, consumption value, and brand image on repurchase intention of traditional Balinese fusion food at restaurants in Bali province. The population in this study consists of all individuals who have purchased traditional Balinese fusion food or traditional Balinese food that has undergone adaptation more than twice. The sample size for this research is 170 people who have made at least two purchases of traditional Balinese fusion food to ensure objective results and reflect the actual situation. The data collection method in this study was conducted through questionnaires using a Likert scale. Based on the hypothesis testing results, the findings show that green marketing and brand image each have a significant impact on repurchase intention of traditional Balinese fusion food with significance values of Sig. <0.001 and Sig. 0.02, respectively, while consumption value has no significant effect on repurchase intention with a significance value of Sig. 0.278. Green marketing, consumption value, and brand image simultaneously have a significant effect on repurchase intention of traditional Balinese fusion food with a significance value of Sig. 0.000.